1923
DOI: 10.1017/s0022172400008044
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Passive Immunity. Part III

Abstract: 1. The course of disappearance of passive immunity in rabbits injected with diphtheria antitoxin obtained from goats, men, guinea-pigs and cows, consists of the same three phases that follow the injection of horse serum.2. The rabbits examined were more responsive to goat, human and guinea-pig serum than to horse and cow serum.3. The course of disappearance of passive immunity in rabbits, horses and guinea-pigs injected with homologous antitoxin, consists of Phases A and B only, and Phase B is far slower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1925
1925
1977
1977

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The best examples to record are those of certain normal horses that were injected with diphtheria antitoxin obtained from other horses and the rate of loss of the passive immunity so conferred was determined by tests upon samples of blood taken at weekly intervals from these horses. Some of these results have already been published by Glenny and Hopkins (1923) who showed that the course of loss of passive immunity is such that the logarithms of the antitoxic titre of the horse fall upon a straight line such as that, 980 (I), shown on chart 2 for the first injection of horse 980. Tbis horse before its injection with antitoxic serum contained less than 0'0005 unit per C.C.…”
Section: XXVIIImentioning
confidence: 85%
See 1 more Smart Citation
“…The best examples to record are those of certain normal horses that were injected with diphtheria antitoxin obtained from other horses and the rate of loss of the passive immunity so conferred was determined by tests upon samples of blood taken at weekly intervals from these horses. Some of these results have already been published by Glenny and Hopkins (1923) who showed that the course of loss of passive immunity is such that the logarithms of the antitoxic titre of the horse fall upon a straight line such as that, 980 (I), shown on chart 2 for the first injection of horse 980. Tbis horse before its injection with antitoxic serum contained less than 0'0005 unit per C.C.…”
Section: XXVIIImentioning
confidence: 85%
“…It was pointed out (Glenny and Hopkins, 1923) that horse 982 " still showed a high antitoxic content over 40 weeks after injection and little or no loss occurred from the 29th to the 40th weeks and then a marked increase in antitoxic value was seen. The various readings of the antitoxic content plot.ted against time do not fall upon a straight line.…”
Section: XXVIIImentioning
confidence: 99%
“…Dealing with the first of these problems, Glenny & Hopkins (1922, 1923, working with diphtheria antitoxin prepared in horses, showed that sensitized rabbits eliminated the antitoxin more rapidly than normal animals. Similar results have been recorded by Talmage, Dixon, Bukantz & Danmmin (1951 using 1311-labelled serum proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty years ago Glenny (1) and Freund (2) and their coworkers demonstrated that passively infused antibody disappeared from the plasma of the recipient due to the combined effects of distribution and catabolism of these molecules. Subsequently, Schoenheimer (3) demonstrated that the other body proteins do not serve the organism for life but are continually being degraded and replaced by newly synthesized molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Schoenheimer (3) demonstrated that the other body proteins do not serve the organism for life but are continually being degraded and replaced by newly synthesized molecules. The objectives of this review are: (1) to describe the physiological factors affecting albumin catabolism and (2) to consider disorders of albumin survival in disease with special reference to those diseases that exemplify the different pathophysiological mechanisms that lead to abnormalities of albumin survival and abnormal serum albumin levels. From the studies with radiolabeled albumin, especially radioiodinated albumin, a general understanding of the normal metabolism of this protein has emerged.…”
Section: Introductionmentioning
confidence: 99%